Identification of Pantoea ananatis strain BCA19 as a potential biological control agent against Erwinia amylovora - Lee, Jueun; Jung, Won-Kwon; Ahsan, S. M.; Jung, Hee-Young; Choi, Hyong Woo (Frontiers in Microbiology, 2024)
In this study, we aimed to screen potential antagonistic microorganisms against Erwinia amylovora, the causal agent of fire blight. From 127 unknown bacterial isolates tested, 2 bacterial strains (BCA3 and BCA19) were identified to show distinct antagonistic activity against E. amylovora in agar plate assay. Phylogenetic analysis of the 16s rRNA sequence identified both BCA3 and BCA19 as Pantoea ananatis. Among these BCA19 showed 13.9% stronger antagonistic activity than BCA3. Thus we further characterized antagonistic activity of BCA19. Culture filtrates (CF) of BCA19 significantly inhibited the swimming and swarming motility of E. amylovora. Ethyl acetate and n-butanol extracts of CF of BCA19 exhibited antibacterial activity in disk diffusion assay. Furthermore, gas chromatography–mass spectrometry analysis of ethyl acetate and n-butanol extracts of CF of BCA19 identified antibacterial compounds, including indole and hexahydropyrrolo[1,2-a]pyrazine-1,4-dione. Importantly, indole inhibited growth of E. amylovora with IC50 value of 0.109 ± 0.02 mg/mL ( 930.4 μM). Whole genome sequence analysis of BCA 19 revealed gene clusters related with siderphore, andrimid, arylpolyene and carotenoid-type terpene production. This study indicates that BCA19 can be used as a potential biological control agent against Erwinia amylovora.